Photoelectron holography of atomic targets - Borbély, S. (2019)
We study the spatial interference effects appearing during the ionization of atoms (H, He, Ne, and Ar) by few-cycle laser pulses using single-electron ab initio calculations. The spatial interference is the result of the coherent superposition of the electronic wave packets created during one half cycle of the driving field following different spatial paths. This spatial interference pattern may be interpreted as the hologram of the target atom. With the help of a wave-function analysis (splitting) technique and approximate (strong-field and Coulomb-Volkov) calculations, we directly show that the hologram is the result of the electronic-wave-packet scattering on the parent ion. On the He target we demonstrate the usefulness of the wave-function splitting technique in the disentanglement of different interference patterns. Further, by performing calculations for the different targets, we show that the pattern of the hologram does not depend on the angular symmetry of the initial state and it is strongly influenced by the atomic species of the target: A deeper bounding potential leads to a denser pattern.